Implementation of the neurological skills ambulatory in medical graduation: practices and reflections (Research, Society and Development, 2022)
Medical education in Brazil is heterogeneous and has undergone a reformulation in recent decades. Activities were resized and the role of specialty clinics needs to be frequently revisited. Neurological patients have become frequent in primary care and professional training needs to address this scenario. The study aims to describe the experience of implementing an academic neurology outpatient clinic, as well as the teaching-learning process developed in the Medicine course at a university in the interior of the Amazon, and to suggest solutions to the problems encountered. It is a descriptive study, in the form of an experience report, with a qualitative approach. Most students had difficulties with content related to neurological diseases and performing the neurological exam, with progressive evolution over the months. The diagnostic reasoning had a satisfactory level and also progressed. The most persistent problems were related to time management, description in the medical record, preparation of prescription and communication of diagnosis and prognosis. The assessment methods used in the outpatient clinic were self-assessment, immediate feedback, structured objective clinical examination (OSCE) and summative assessment through analysis of videos of real or simulated patients. The assessment was satisfactory for most. It was concluded that the neurology outpatient clinic is an important setting for the integration of teaching, care and the development of skills necessary for professional practice.